PENGARUH INSTAGRAM TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN PPKN SMAN PONTIANAK - Indah Sari Putri; Bambang Budi Utomo; Thomy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was using descriptive research method with the form of quantitative. The Source of this research is Students of X IIS 3 and the data collection tool is questionnaires. The content of the questionnaires frankly enclosed the questions about Instagram users and cognitive data results of Students’ exam in first semester, the research also conducted by doing the interview of Pancasila and Civic Education teacher and X IIS 3’s students. The result revealed that the calculation and data processing showed the value of R as much as 0,620. The conclusion that we can take from the research is Instagram as social media affected the grade of students, although the value of effect is  strong. Based on the table shown in the research, the researcher got the value of R Square in 0,620 or 62 % which interpreted as the effect of Instagram is only 62 % toward Students’ grade of X IIS 3 in SMAN 7 Pontianak in PPKn, the rest of numbers that are not mentioned are affected by other factors which give effects toward Y variable. Based on coefficient of Determination’s calculation, It clearly explained that Social Media Instagram gave “a strong” effect on Student’s grade. Keywords: Instagram, Pancasila and Civic Education (PPKn ), Social Media, Student’s Grade, Student.